Implementing physical and virtual food reserves to protect the poor and prevent market failure - von Braun, Joachim; Torero, Máximo (International Food Policy Research Institute, 2009)
The 2007–08 international food price crisis caused hardship on a number of fronts. The steep rise in food prices led to economic difficulties for the poor and generated political turmoil in many countries. The crisis could also result in long-term, irreversible nutritional damage, especially among children. There is a global interest in preventing such events from recurring. The price crisis was triggered by a complex set of long-term and short-term factors, including policy failures and market overreactions. One important factor in the crisis was the entry of significant financial resources into futures markets, including food commodity markets, which contributed to a price spike during the first six months of 2008. This episode highlights the need to modify the architecture of international financial and agricultural markets to address the problem of price spikes, especially their effects on the livelihoods of the poor. Although a set of guiding principles for regulating agricultural and commodity futures markets should be developed and recent inappropriate trade policy instruments such as export bans should be reviewed, these actions are not sufficient to avoid extreme price spikes and to ensure that the world can respond to emergency needs for food. We propose two global collective actions to meet these goals. First, a small physical food reserve should be established to facilitate a smooth response to food emergencies. Second, an innovative virtual reserve should be set up to help prevent market price spikes and to keep prices closer to levels suggested by long-run market fundamentals like supply and demand. This brief offers some specifics on implementing a proposal described in our earlier IFPRI policy brief titled Physical and Virtual Global Food Reserves to Protect the Poor and Prevent Market Failure (June 2008). Price instability is a general feature of agricultural markets. The proposals made here are designed not to stabilize prices generally, but to prevent damaging price spikes. The proposed actions will entail costs, but the modest costs of the required organizational elements must be balanced against the benefits of more effective international financial architecture. These benefits will include prevention of economic hardship, improved market efficiency, stronger incentives for long-term investment in agriculture, and prevention of political instability.